Affability in Abdulkarim Khiratullah’s Novel Mencari Cinta Yang Hilang - ., Verawati (KnE Social Sciences, 2018)
This paper is concerned with the Protagonist’s affability in Abdulkarim Khiratullah’s Novel Mencari Cinta yang Hilang. The Goals are to reveal the kinds of affabilities in the novel and to describe the application of the protagonist’s affabilities in the novel. The method used in this research is descriptive qualitative method proposed by Sugiyono (2012). Descriptive means to describe something such as: circumstance, situation, condition, event, action, etc. The primary data source in this study is derived from the novel Mencari Cinta yang Hilang by Abdulkarim Khiratullah consisting of words, phrases, and sentences illustrating the affabilities of the protagonist. While the secondary data source is taken from books, journal and websites including references related to this study. There are some theories used as reference in this study, but among those theories, the affability proposed by Budiningsih (2004) is applied to analyze the affability in the novel Mencari Cinta yang Hilang written by Abdulkarim Khiratullah. Based on the analysis, it is found that the moral values of the protagonist in the novel are: Empathy, Obedience and Patience. Keywords: affability, empathy, obedience, patience.